Food Consumption by Health Care Workers of Sverdlovsk Region (on Budget Studies of 1957) - V. N. Mamyachenkov (Научный диалог)
The article is devoted to the subject insufficiently developed in the national historiography. The study is conducted on materials of State archive of Sverdlovsk region and archive of the Territorial body of Federal state statistics service for Sverdlovsk region with the assistance of scientific and statistic literature. The relevance of the topic is determined by its importance for the social sciences. The study of the level of food consumption by health care workers of the Sverdlovsk region in 1957 is made. Scientific novelty of the research is seen in the fact that the new materials discovered by the author in mentioned archives are introduced into scientific usage. It is noted that proposed work continues the already published author’s article devoted to the monetary income of health workers. It is stated that for the “minor” categories of the population (primary and secondary school teachers, doctors, nurses and others), the statistical authorities usually propose low-representative samples. It is emphasized that neither people under studying, nor their family members were not abusing alcoholic beverages. It is stated that there was a rather serious differentiation of the surveyed health workers in terms of food consumption. It is argued that the level of their food consumption, taking into account the situation in the country, should be assessed: for physician - as generally sufficient, for other respondents - as insufficient. It is concluded that the level of consumption of food was significantly lower than scientifically based standards.